UiTM Sarawak academic missions to Bintulu and Kabong - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
UiTM Sarawak Academic Missions to Bintulu and Kabong districts were held from 21 October to 27 October 2008. A team of lecturers was sent to these districts for both events. The warm response from students and teachers of various schools in Bintulu were very encouraging and heart-warming. There were more than twenty Public and Private Universities and relevant Government Agencies participated in the exhibition. The event was well organized. The team then, moved ahead to the next academic mission in Kabong after they left Bintulu.